ANALISIS PENGARUH BELANJA NEGARA TERHADAP INFLASI DAN PERTUMBUHAN EKONOMI - Slamet Widodo; Dahiri Dahiri (Pusat Kajian Anggaran, 2016)
State expenditure continue to increase every year. The increasing number is expected to boost the economic growth. However, it can not be ascertained whether it has a positive or negative influence to economic growth. They depends on government policy. The results of the analysis explained that state expenditure has one way effects to economic growth and inflation.